Toward a better definition of focal cortical dysplasia: An iterative histopathological and genetic agreement trial. (5th May 2021) - Blümcke, Ingmar; Coras, Roland; Busch, Robyn M.; Morita‐Sherman, Marcia; Lal, Dennis; Prayson, Richard; Cendes, Fernando; Lopes‐Cendes, Iscia; Rogerio, Fabio; Almeida, Vanessa S.; Rocha, Cristiane S.; Sim, Nam Suk; et al.
Abstract: Objective: Focal cortical dysplasia (FCD) is a major cause of difficult‐to‐treat epilepsy in children and young adults, and the diagnosis is currently based on microscopic review of surgical brain tissue using the International League Against Epilepsy classification scheme of 2011. We developed an iterative histopathological agreement trial with genetic testing to identify areas of diagnostic challenges in this widely used classification scheme. Methods: Four web‐based digital pathology trials were completed by 20 neuropathologists from 15 countries using a consecutive series of 196 surgical tissue blocks obtained from 22 epilepsy patients at a single center. Five independent genetic laboratories performed screening or validation sequencing of FCD‐relevant genes in paired brain and blood samples from the same 22 epilepsy patients. Results: Histopathology agreement based solely on hematoxylin and eosin stainings was low in Round 1, and gradually increased by adding a panel of immunostainings in Round 2 and the Delphi consensus method in Round 3. Interobserver agreement was good in Round 4 (kappa = .65), when the results of genetic tests were disclosed, namely, MTOR, AKT3, and SLC35A2 brain somatic mutations in five cases and germline mutations in DEPDC5 and NPRL3 in two cases. Significance: The diagnoses of FCD 1 and 3 subtypes remained most challenging and were often difficult to differentiate from a normal homotypic or heterotypic cortical architecture. Immunohistochemistry was helpful, however, to confirm the diagnosis of FCD or no lesion. We observed a genotype–phenotype association for brain somatic mutations in SLC35A2 in two cases with mild malformation of cortical development with oligodendroglial hyperplasia in epilepsy. Our results suggest that the current FCD classification should recognize a panel of immunohistochemical stainings for a better histopathological workup and definition of FCD subtypes. We also propose adding the level of genetic findings to obtain a comprehensive, reliable, and integrative genotype–phenotype diagnosis in the near future.